The Influence of The Intensity of Social Media Use and Peer Group Communication Towards Fear of Missing Out on Late Adolescents - Afra, Adeela; Ratri Rahmiaji, Lintang; Luqman, Yanuar (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Indonesian late adolescents are actively involved in social media, experiencing both positive and negative effects. On the positive side, they gain knowledge, access useful information, find inspiration, and engage in meaningful interactions. Conversely, they also face negatives such as heightened anxiety, social comparison, exposure to misinformation, and mental health challenges. This study explores how social media engagement and peer group communication contribute to Fear of Missing Out (FOMO) in late adolescents.FOMO has emerged as a significant concern with the rise of social media and digital technology, intensifying the fear of being excluded from social experiences and trends. The research focuses on the influence and correlation between social media use intensity and peer group communication regarding FOMO in late adolescents aged 18-21. Employing a quantitative approach with 100 respondents and a simple linear regression test, the findings consistently indicate that as social media usage increases, weaken the likelihood of experiencing FOMO. Notably, heightened communication among peers corresponds with a decreased likelihood of FOMO.To enhance future research, it is recommended to incorporate additional variables such as comparison tendencies, self-esteem levels, personality traits, and peer pressure, contributing further to the understanding of FOMO. Qualitative research methods, like interviews or focus groups, could offer deeper insights into individuals' subjective experiences related to FOMO, complementing quantitative findings with context. Additionally, broadening the age range and demographic characteristics of participants would provide a more comprehensive understanding of how FOMO manifests across diverse life stages within the context of social media usage.